Pengaruh Brand Experience Dan E-Service Quality Terhadap Brand Loyalty (Survei Pada Konsumen Toko Ansthelabel Tasikmalaya) - Ratih Purnamasari; Depy Muhamad Pauzy; Ari Arisman (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to determine the simultaneous and partial effect of Brand Experience and E-Service Quality on Brand Loyalty in Anthelabel Tasikmalaya Shop Consumers. Descriptive research method with a survey approach. The population in this research is Ansthelabel consumers as many as 100 consumers. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of the study show that Brand Experience and E-Service Quality simultaneously have a significant effect on Brand Loyalty for Ansthelabel Tasikmalaya Store consumers. Partially, Brand Experience has a significant effect on Brand Loyalty for consumers at Ansthelabel Tasikmalaya Store. Partially, E-Service Quality has a significant effect on Brand Loyalty for consumers at Ansthelabel Tasikmalaya Store.